Hubungan Pengetahuan Keluarga Tentang Tanda Dan Gejala Skizofreniaparanoid Dengan Upaya Mencegah Kekambuhan PasienDi RSJD Surakarta - YAQIN, TAUFIQ FAHMI; , Arif Widodo, A.Kep., M.Kes; , Endang Zu laicha Susilaningsih, S.Kp (2015)
Treatment of patients with mental disorders has not been satisfactory, it was especially true in developing countries, due to ignorance family and the community against this type of mental disorder was still the presence of such a negative view (stigma) and that a mental disorder was not an illness that can be treated and cured. Both of the above led to people with mental disorders experience discrimination and were not getting adequate help. This study aims to determine the relationship of family knowledge about the signs and symptoms of paranoid schizophrenia with efforts to prevent relapse in patients in the Outpatient Installation at Mental Hospital of Surakarta in 2013. This research was quantitative research with cross sectional approach. The samples were 87 families client outpatient at RSJD Outpatient Installation in Surakarta. Data processing techniques using Chi Square technique. The conclusions of this study were: (1) family knowledge about the signs and symptoms of relapse of schizophrenia paranoid was largely sufficient (48%), (2) efforts to prevent the recurrence of schizophrenia paranoid was largely sufficient (47%), and (3) there was a significant relationship between knowledge of the signs and symptoms of paranoid skizofreia with efforts to prevent relapse in patients skizofreia paranoid Outpatient Installation RSJD Surakarta (p-value = 0,000).